Level of job satisfaction and associated factors among health care professionals working at University of Gondar Referral Hospital, Northwest Ethiopia: a cross-sectional study - Getnet Gedif; Yetnayet Sisay; Animut Alebel; Yihalem Abebe Belay (BMC Research Notes, 2018)
Abstract Objectives The main aim of this study was to assess the level of job satisfaction and associated factors among healthcare professionals working at University of Gondar Referral Hospital, Northwest Ethiopia. An institution based cross-sectional study was conducted among 416 healthcare professionals from March 27, 2017 to April 25, 2017. Simple random sampling technique was employed and data were collected with a pre-tested interviewer administered questionnaire. Data were entered into Epi-Info version 7, and analyzed using SPSS 20 softwares. Binary logistic regression analysis was employed. Results A total of 383 participants were involved in the study. The overall level of job satisfaction among health care professionals was 54% [95% CI (49.3–58.8)]. Marital status [AOR = 1.79 (1.140, 2.797)], salary [AOR = 2.75 (1.269, 5.958)], leadership style [AOR = 2.19 (1.31–3.65)], and supportive supervision [AOR = 2.05 (1.27–3.32)] were found significant determinants of job satisfaction. The overall level of job satisfaction among health care professionals at the University of Gondar Referral Hospital was low. Therefore, health service managers should focus their leadership style and provide supportive supervision in the hospital to improve the level of job satisfaction of health care professionals.